Human Resource Management Practices, employee satisfaction and employee desire to quit. The case of Shisong Hospital in Kumbo Cameroon - Berinyuy, Benard (Technium Social Sciences Journal, 2021)
Human resource management practices, employee satisfaction and employee desire to quit are some key concepts that organisations, especially those of the health service industry must uphold in order to have a better competitive position in the volatile business environment. It is common to find employees moving from one health facility to the other, in search for better human resource management practices; while these facilities fight for better performance. An investigation of the practical relationships among these concepts has been done for St Elisabeth Catholic General hospital (SECGH) Shisong (Shisong Hospital), which is based in Kumbo in the Northwest province of Cameroon as an x-ray for other hospitals to follow. Primary data was collected from 166 employees through a uniquely designed questionnaire. Secondary Quantitative (Chi square correlation) analysis was done to see if relationships exist among these concepts in Shisong hospital. It was found that there is a significant positive relationship between Human Resource Management Practices and employee satisfaction; and that there was no significant relationship between human resource management practices and employee intention to quit,; no significant relationship between employee satisfaction and employee intention to quit. Shisong hospital should improve on its human resource management practices to gain a better competitive position in the health service business.